2007
DOI: 10.1557/jmr.2007.0320
|View full text |Cite
|
Sign up to set email alerts
|

Possible new single-buffer layers for YBa2Cu3O7−y coated conductors prepared by chemical solution deposition

Abstract: New single-buffer layers of YBiO3 and SmBiO3 have been proposed for YBa2Cu3O7−y (YBCO) and SmBa2Cu3O7−y coated conductors. Highly c-axis oriented YBiO3 and SmBiO3 buffer layers have been deposited on single-crystal LaAlO3 and SrTiO3, respectively, by a low-cost chemical solution deposition method in a temperature range as low as 730 to 800 °C in air. Precursor solution of yttrium nitrate, samarium nitrate, and bismuth nitrate has been deposited using spin coating and heat treated in air in a single stage to yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Namely, it is reported from band structure calculations that YBiO 3 in the cubic perovskite structure with this 4.405Å lattice parameter and Bi at the octahedral site is about 2.50 eV/atom above the lowest-energy structure and therefore unlikely to be stable. [83] This value of 4.405Å is much smaller than the reported value of 5.428Å [82] lacking discussion on the actual crystal structure. This value of 5.428 is subsequently erroneously [84] assigned to a perovskite structure predicting YBiO 3 to be a topological insulator.…”
Section: Structural Characterisationmentioning
confidence: 67%
See 1 more Smart Citation
“…Namely, it is reported from band structure calculations that YBiO 3 in the cubic perovskite structure with this 4.405Å lattice parameter and Bi at the octahedral site is about 2.50 eV/atom above the lowest-energy structure and therefore unlikely to be stable. [83] This value of 4.405Å is much smaller than the reported value of 5.428Å [82] lacking discussion on the actual crystal structure. This value of 5.428 is subsequently erroneously [84] assigned to a perovskite structure predicting YBiO 3 to be a topological insulator.…”
Section: Structural Characterisationmentioning
confidence: 67%
“…From theoretical and experimental results it is concluded that (Y x Bi 1−x ) 2 O 3 with x = 0.2-0.5 has a cubic lattice constant of ∼5.4Å, with a defective fluorite type crystal structure with space group Fm3m. [80][81][82]11 Therefore the observed peaks at 33.4 • and 28.8 • are assigned to respectively YBiO 3 (002) and YBiO 3 (111) reflections assuming this cubic fluorite structure, 12 which translate to an out-of-plane lattice constant of 5.360Å. 10 This is supported by XPS compositional characterisation discussed in the next section.…”
Section: Structural Characterisationmentioning
confidence: 72%
“…In order to lower the sintering temperature of the buffer layer for coated conductors in CSD processing, a class of new buffer materials, REBiO 3 (RE correspond to a rare earth element), were developed, and their physical and chemical property were systematically characterized [11,12]. A REBiO 3 buffer layer can be epitaxially grown at a relatively low temperature of around 700-900 • C [12][13][14][15][16][17] because of its low formation temperature. Lowering the processing temperature not only means saving energy and reducing cost, but can also avoid or reduce some of the difficulties of manufacturing coated conductors, e.g., avoiding mechanical strength degradation at high temperatures for metal substrates and reducing chemical diffusion in the interface of the buffer layer and substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, once formed, the REBiO 3 buffer layer possesses very good thermal stability as studied via thermal decomposition experiments in different oxygen partial pressures for YBiO 3 (YBO) precursor powders [13]. Taking these advantages, YBO and SmBiO 3 (SBO) films have been successfully grown in air [14,15]. GdBiO 3 (GBO) and DyBiO 3 (DBO) films have also been successfully grown in argon gas [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to obtain highly textured REBCO coated conductors, many buffer layer materials have been identified including SrTiO 3 [8], La 2 Zr 2 O 7 [9,10], CeO 2 [11,12], RE 2 O 3 [13][14][15] and REBiO 3 [16][17][18][19]. As a promising candidate of buffer layer material for YBCO coated conductors, CeO 2 has been prepared by many groups due to its excellent chemical compatibility with Ni-based alloy substrates as well as good lattice match with YBCO or REBCO.…”
Section: Introductionmentioning
confidence: 99%